Buty and the beast: the complex role of butyrate in Parkinson’s disease - Elford, Joshua D.; Becht, Nanette; Garssen, Johan; Kraneveld, Aletta D.; Perez-Pardo, Paula (Frontiers in Pharmacology, 2024)
Parkinson's disease (PD) is a complex neurodegenerative disease which is often associated with gastrointestinal (GI) dysfunction. The GI tract is home to a wide range of microorganisms, among which bacteria, that can influence the host through various mechanisms. Products produced by these bacteria can act in the gut but can also exert effects in the brain via what is now well established to be the microbiota-gut-brain axis. In those with PD the gut-bacteria composition is often found to be different to that of non-PD individuals. In addition to compositional changes, the metabolic activity of the gut-microbiota is also changed in PD. Specifically, it is often reported that key producers of short chain fatty acids (SCFAs) as well as the concentration of SCFAs themselves are altered in the stool and blood of those with PD. These SCFAs, among which butyrate, are essential nutrients for the host and are a major energy source for epithelial cells of the GI tract. Additionally, butyrate plays a key role in regulating various host responses particularly in relation to inflammation. Studies have demonstrated that a reduction in butyrate levels can have a critical role in the onset and progression of PD. Furthermore, it has been shown that restoring butyrate levels in those with PD through methods such as probiotics, prebiotics, sodium butyrate supplementation, and fecal transplantation can have a beneficial effect on both motor and non-motor outcomes of the disease. This review presents an overview of evidence for the altered gut-bacteria composition and corresponding metabolite production in those with PD, with a particular focus on the SCFA butyrate. In addition to presenting current studies regarding SCFA in clinical and preclinical reports, evidence for the possibility to target butyrate production using microbiome based approaches in a therapeutic context is discussed.